Структурний аналіз системи управління організаційною автономією університету - Раєвнєва, Олена Валентинівна; Степуріна, Світлана Олександрівна (ВД "ІНЖЕК", 2018)
Метою статті є структурний аналіз якості функціонування системи управління організаційною автономією закладу вищої освіти за допомогою інструментарію системного аналізу. Проведений аналіз сучасних досліджень щодо розвитку університетської автономії у вітчизняних ЗВО дозволив виявити, що саме аналізу організаційних структур управління університетською автономією спеціальними методами приділяється недостатньо уваги. У результаті дослідження виявлено деякі особливості та недоліки в системі управління організаційною автономією ЗВО, визначено її слабкі місця, запропоновано переглянути складові структури та її зв'язки з метою більш ефективного її функціонування. Перспективою подальших досліджень у даному напрямку є аналіз структур управління різними видами університетської автономії з метою ефективного управління, шляхом розробки та впровадження адекватних управлінських впливів за різними напрямками та видами автономій.

The article is aimed at the structural analysis of quality of performance of the management system of organizational autonomy of higher educational institution using the instrumentarium of systems analysis. The carried out analysis of topical researches on development of university autonomy in the national higher educational institutions allowed to identify that especially the analysis of organizational management structures of university autonomy is given insufficient attention. The study resulted in identifying some specific characteristics and shortcomings in the management system of organizational autonomy of university, defining its weaknesses, it is suggested that the components of the structure and its connection be revised with the purpose of more effectively performance. Prospect for further research in this direction is analysis of the systems of management of different types of university autonomy with a view to an efficient management, through the development and implementation of adequate managerial influences in different directions and according to types of autonomies.
The structural analysis of the management systems of organizational autonomy of University
Keywords: освітні корпорації; керівники; управлінська діяльність; джерела доходів; управлінські впливи; organizational autonomy of university; expansion of autonomy; structural analysis; management system of organizational autonomy